Species Assembly Is Lineage Specific: Phylogenetic Divergent Species Aggregate in Some Lineages but Segregate in Others - Keliang Zhang; Alexander J. Fergus; Lou Barbe; Bernhard Schmid; Eric Allan; Tania Jenkins; Christiane Roscher; Thomas Leclère; Igor V. Bartish; Andreas Prinzing (Ecology Letters, 2026)
Phylogenetic divergence between species may weaken both negative and positive biotic interactions. Whether, as a result, divergent species aggregate or segregate remains unclear. These interactions differ among lineages, and without immigration, the effects of interactions might be overridden by dispersal limitation. We studied changes in co‐occurrence across 5 years for 1770 pairs of grassland species drawn primarily from four major lineages (families), reducing dispersal limitation by seed addition. Across all lineages, changes in co‐occurrence were almost unrelated to phylogenetic divergence, partly reflecting opposing relationships within two groups of families: Fabaceae/Poaceae, where more divergent species segregated, versus Asteraceae/Apiaceae, where they aggregated. Dispersal limitation through lack of immigration existed, without eliminating divergence effects. We conclude that species assembly differed between major lineages, with spatial aggregation in Asteraceae/Apiaceae possibly reflecting limiting similarity, whereas segregation in Fabaceae/Poaceae may reflect mutualist incompatibility or asymmetric competition. These processes could feedback on within‐lineage diversification.

Why Some Habitat Types Are Locally Much More Species‐Rich Than Others: Ongoing Assembly of Species Produced by Long and Rapid Macroevolutionary Diversification - Andreas Prinzing; Igor V. Bartish; Keliang Zhang; Benjamin Yguel (Global Ecology and Biogeography, 2025)
Aim Species richness of local communities is often considered to be disconnected from the macroevolutionary diversification of lineages operating at much larger spatiotemporal scales. However, local communities occupy patches of habitat types, many of which persist across large spatiotemporal scales. We hypothesise that high local species richness of specific habitat types could result from ongoing local assembly in which both very closely related and very distantly related species can locally co‐occur. Alternatively, such local richness of specific habitat types could result from historical assembly in which historical colonisation by many lineages and diversification within habitat‐type increased richness of the habitat species‐pool and thereby the local communities sampled from it. Location The Netherlands. Time Period 1932–2012. Major Taxa Studied Angiosperms. Methods We analysed 6851 small‐scale local plots (median 54 m 2 ) belonging to all major habitat types in the Netherlands. We quantified mean pairwise phylogenetic distances across all species and between phylogenetically nearest species, standardised for 0‐expectations for a given species richness. We quantified these measures for local communities, averaged within habitat types and for the species‐pools of the habitat types. Results Local richness varied 21‐fold among habitat types. Local richness increased with mean pairwise distances and decreased with mean nearest‐taxon distances of local communities (but not of habitat species‐pools). These patterns were independent of the size of the regional habitat species‐pool, the presence of exotic species and the environmental conditions. Main Conclusions Local species richness varies massively among habitat types within a region. We suggest that some habitat types are locally species rich because today they permit the most distantly related and the most closely related species to coexist, likely through stabilising and equalising mechanisms, respectively. These mechanisms should be tested in the future.

Simulated Herbivory Affects the Volatile Emissions of Oak Saplings, while Neighbourhood Affects Flavan-3-ols Content of Their Leaves - Freerk Molleman; Manidip Mandal; Anna Sokół-Łętowska; Urszula Walczak; Martin Volf; Soumen Mallick; Martin Moos; Petr Vodrážka; Andreas Prinzing; Priscila Mezzomo (Journal of Chemical Ecology, 2024)

Decomposing drivers in avian insectivory: Large‐scale effects of climate, habitat and bird diversity - Laura Schillé; Elena Valdés‐Correcher; Frédéric Archaux; Flavius Bălăcenoiu; Mona Chor Bjørn; Michal Bogdziewicz; Thomas Boivin; Manuela Branco; Thomas Damestoy; Maarten de Groot; Jovan Dobrosavljević; Mihai‐Leonard Duduman; et al. (Journal of Biogeography, 2024)
Aim Climate is a major driver of large‐scale variability in biodiversity, as a likely result of more intense biotic interactions under warmer conditions. This idea fuelled decades of research on plant‐herbivore interactions, but much less is known about higher‐level trophic interactions. We addressed this research gap by characterizing both bird diversity and avian predation along a climatic gradient at the European scale. Location Europe. Taxon Insectivorous birds and pedunculate oaks. Methods We deployed plasticine caterpillars in 138 oak trees in 47 sites along a 19° latitudinal gradient in Europe to quantify bird insectivory through predation attempts. In addition, we used passive acoustic monitoring to (i) characterize the acoustic diversity of surrounding soundscapes; (ii) approximate bird abundance and activity through passive acoustic recordings; and (iii) infer both taxonomic and functional diversity of insectivorous birds from recordings. Results The functional diversity of insectivorous birds increased with warmer climates. Bird predation increased with forest cover and bird acoustic activity but decreased with mean annual temperature and functional richness of insectivorous birds. Contrary to our predictions, climatic clines in bird predation attempts were not directly mediated by changes in insectivorous bird diversity or acoustic activity, but climate and habitat still had independent effects on predation attempts. Main Conclusions Our study supports the hypothesis of an increase in the diversity of insectivorous birds towards warmer climates but refutes the idea that an increase in diversity would lead to more predation and advocates for better accounting for activity and abundance of insectivorous birds when studying the large‐scale variation in insect‐tree interactions.

Ectophagous folivores do not profit from rich resources on phylogenetically isolated trees - Soumen Mallick; Freerk Molleman; Benjamin Yguel; Richard Bailey; Jörg Müller; Frédéric Jean; Andreas Prinzing (Oecologia, 2023)

Drivers of taxonomic, functional and phylogenetic diversities in dominant ground-dwelling arthropods of coastal heathlands - Axel Hacala; Denis Lafage; Andreas Prinzing; Jérôme Sawtschuk; Julien Pétillon (Oecologia, 2021)

Search for top‐down and bottom‐up drivers of latitudinal trends in insect herbivory in oak trees in Europe - Elena Valdés‐Correcher; Xoaquín Moreira; Laurent Augusto; Luc Barbaro; Christophe Bouget; Olivier Bouriaud; Manuela Branco; Giada Centenaro; György Csóka; Thomas Damestoy; Jovan Dobrosavljević; Mihai‐Leonard Duduman; et al. (Global Ecology and Biogeography, 2021)
Aim The strength of species interactions is traditionally expected to increase toward the Equator. However, recent studies have reported opposite or inconsistent latitudinal trends in the bottom‐up (plant quality) and top‐down (natural enemies) forces driving herbivory. In addition, these forces have rarely been studied together thus limiting previous attempts to understand the effect of large‐scale climatic gradients on herbivory. Location Europe. Time period 2018–2019. Major taxa studied Quercus robur . Methods We simultaneously tested for latitudinal variation in plant–herbivore–natural enemy interactions. We further investigated the underlying climatic factors associated with variation in herbivory, leaf chemistry and attack rates in Quercus robur across its complete latitudinal range in Europe. We quantified insect leaf damage and the incidence of specialist herbivores as well as leaf chemistry and bird attack rates on dummy caterpillars on 261 oak trees. Results Climatic factors rather than latitude per se were the best predictors of the large‐scale (geographical) variation in the incidence of gall‐inducers and leaf‐miners as well as in leaf nutritional content. However, leaf damage, plant chemical defences (leaf phenolics) and bird attack rates were not influenced by climatic factors or latitude. The incidence of leaf‐miners increased with increasing concentrations of hydrolysable tannins, whereas the incidence of gall‐inducers increased with increasing leaf soluble sugar concentration and decreased with increasing leaf C : N ratios and lignins. However, leaf traits and bird attack rates did not vary with leaf damage. Main conclusions These findings help to refine our understanding of the bottom‐up and top‐down mechanisms driving geographical variation in plant–herbivore interactions, and indicate the need for further examination of the drivers of herbivory on trees.

Anthropogenic threats to evolutionary heritage of angiosperms in the Netherlands through an increase in high‐competition environments - Igor V. Bartish; Wim A. Ozinga; Mark I. Bartish; G.W. Wieger Wamelink; Stephan M. Hennekens; Benjamin Yguel; Andreas Prinzing (Conservation Biology, 2020)
Present biodiversity comprises the evolutionary heritage of Earth's epochs. Lineages from particular epochs are often found in particular habitats, but whether current habitat decline threatens the heritage from particular epochs is unknown. We hypothesized that within a given region, humans threaten specifically habitats that harbor lineages from a particular geological epoch. We expect so because humans threaten environments that dominated and lineages that diversified during these epochs. We devised a new approach to quantify, per habitat type, diversification of lineages from different epochs. For Netherlands, one of the floristically and ecologically best‐studied regions, we quantified the decline of habitat types and species in the past century. We defined habitat types based on vegetation classification and used existing ranking of decline of vegetation classes and species. Currently, most declining habitat types and the group of red‐listed species are characterized by increased diversification of lineages dating back to Paleogene, specifically to Paleocene‐Eocene and Oligocene. Among vulnerable habitat types with large representation of lineages from these epochs were sublittoral and eulittoral zones of temperate seas and 2 types of nutrient‐poor, open habitats. These losses of evolutionary heritage would go unnoticed with classical measures of evolutionary diversity. Loss of heritage from Paleocene‐Eocene became unrelated to decline once low competition, shade tolerance, and low proportion of non‐Apiaceae were accounted for, suggesting that these variables explain the loss of heritage from Paleocene‐Eocene. Losses of heritage from Oligocene were partly explained by decline of habitat types occupied by weak competitors and shade‐tolerant species. Our results suggest a so‐far unappreciated human threat to evolutionary heritage: habitat decline threatens descendants from particular epochs. If the trends persist into the future uncontrolled, there may be no habitats within the region for many descendants of evolutionary ancient epochs, such as Paleogene.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Evolutionary response to coexistence with close relatives: increased resistance against specialist herbivores without cost for climatic‐stress resistance - Mickael Pihain; Pille Gerhold; Alexis Ducousso; Andreas Prinzing (Ecology Letters, 2019)
Why can hosts coexist with conspecifics or phylogenetically proximate neighbours despite sharing specialist enemies? Do the hosts evolve increased enemy resistance? If so, does this have costs in terms of climatic‐stress resistance, or in such neighbourhoods, does climatic‐stress select for resistances that are multifunctional against climate and enemies? We studied oak ( Quercus petraea ) descendants from provenances of contrasting phylogenetic neighbourhoods and climates in a 25‐year‐old common garden. We found that descendants from conspecific or phylogenetically proximate neighbourhoods had the toughest leaves and fewest leaf miners, but no reduction in climatic‐stress resistance. Descendants from such neighbourhoods under cold or dry climates had the highest flavonol and anthocyanin levels and the thickest leaves. Overall, populations facing phylogenetically proximate neighbours can rapidly evolve herbivore resistance, without cost to climatic‐stress resistance, but possibly facilitating resistance against cold and drought via multifunctional traits. Microevolution might hence facilitate ecological coexistence of close relatives and thereby macroevolutionary conservatism of niches.

A forest canopy as a living archipelago: Why phylogenetic isolation may increase and age decrease diversity - Jose Hidasi‐Neto; Richard I. Bailey; Chloe Vasseur; Steffen Woas; Werner Ulrich; Olivier Jambon; Ana M. C. Santos; Marcus V. Cianciaruso; Andreas Prinzing (Journal of Biogeography, 2019)
Aim An individual tree resembles a living island, a small spatially distinct unit upon which colonizers maintain populations. However, several differences exist compared to oceanic islands: a tree is relatively young, is composed of numerous differently aged branches, may be phylogenetically isolated from neighbours, and some of its colonizers are specific to particular tree lineages. We suggest that these specificities strongly affect both alpha‐ and beta‐diversity within trees, including positive effects of isolation on the diversity of generalists, and strengthening of the effect of isolation with tree age. Location Rennes, Bretagne, Western France Taxon Little‐dispersive, generalist oribatid mites (Acari) and highly dispersive, specialist gall wasps (Hymenoptera: Cynipidae) on oak ( Quercus sp.) trees. Methods We tested the effects of tree and branch age, tree and branch habitat diversity, and tree phylogenetic isolation on per‐branch and per‐tree alpha‐diversity, and on within‐tree beta‐diversity of both taxonomic groups. Results For gall wasps, no variable explained diversity patterns at any level. In contrast, for oribatid mites, we found that high phylogenetic isolation of trees and high branch age increased alpha‐diversity per tree and per branch (in young trees) as well as turnover among branches. High tree age decreased alpha‐diversity per branch (in phylogenetically isolated trees) and increased turnover among branches. Increasing habitat diversity increased alpha‐diversity per tree, but decreased alpha‐diversity per branch (in young trees). Main conclusions For mites, contrary to common expectation, we suggest that: (a) phylogenetically distant neighbours are a source of immigration of distinct species and (b) with the increase of tree age, species‐sorting results in a few species colonizing and dominating their preferred patches. In gall wasps, strict specialization on oaks, and efficient dispersal may render oak age or isolation unimportant. The positive relationship between isolation and within‐tree turnover is a new contribution to biogeography in general.

The island rule of body size demonstrated on individual hosts: phytophagous click beetle species grow larger and predators smaller on phylogenetically isolated trees - Freerk Molleman; Alexandre Depoilly; Philippe Vernon; Jörg Müller; Richard Bailey; Andrea Jarzabek‐Müller; Andreas Prinzing (Journal of Biogeography, 2016)
Aim Under spatial isolation on oceanic islands, species tend to show extreme body sizes. From the point of view of many colonizers, individual hosts surrounded by phylogenetically distant neighbours are phylogenetically isolated. This study addresses for the first time how phylogenetic isolation of individual hosts affects body size of colonizers, and whether effects on body size reflect selection among colonizers established on host individuals rather than selection among colonizers dispersing toward trees or phenotypic plasticity of colonizers. Location Rennes National Forest, Western France. Methods We sampled click beetles (Elateridae) on individual oak trees varying in phylogenetic isolation from their neighbours and in age. We measured body size and fluctuating asymmetry (which we found to correlate to reduced body size) and related both to phylogenetic isolation and age of trees. We compared these relationships among species of different larval trophic position and adult body size, using meta‐analytical approaches. Results Within species, body size changes with phylogenetic isolation of individual host trees: root feeders tend to become larger, predators smaller. Effects were independent of mean body‐size, disappeared with tree age, and were inconsistent with patterns of fluctuating asymmetry. Main conclusions Our results are consistent with body‐size selection among colonizers established on individual trees, rather than selection among colonizers dispersing toward trees or phenotypic plasticity. Overall, phenotype patterns of animals across islands in the ocean may resemble those across host individuals in a phylogenetically distant neighbourhood, suggesting micro‐evolution of colonizers in response to the macro‐evolutionary structure of the host community.

Different habitats within a region contain evolutionary heritage from different epochs depending on the abiotic environment - Igor V. Bartish; Wim A. Ozinga; Mark I. Bartish; G. W. Wieger Wamelink; Stephan M. Hennekens; Andreas Prinzing (Global Ecology and Biogeography, 2016)
Aim Biodiversity hot‐spots are regions containing evolutionary heritage from ancient or recent geological epochs, i.e. evolutionary ‘museums’ or ‘cradles’, respectively. We hypothesize that: (1) there are also ‘museums’ and ‘cradles’ within regions – some species pools of particular habitat types contain angiosperm (flowering plants) lineages from ancient geological epochs, others from recent epochs; (2) habitat‐specific abiotic factors control the number of angiosperm lineages from a given epoch contained in a given habitat species pool. Location The flora of the N etherlands. Methods We studied the world's largest vegetation‐plot database and a new, uniquely resolved dated angiosperm phylogeny available for the N etherlands. We characterized species pools of habitat types by a novel concept: epoch‐specific lineage diversities. Results We found that species pools of most habitat types were characterized by over‐ or underrepresentation of lineages from at least one epoch, dating back to the origin of angiosperms. These patterns are not captured by mean lineage ages. Abiotic environments explained on average 56% and up to 75% of the variance in the number of lineages per epoch, but with opposing effects of the same factor for different epochs. Specifically, warm and dry habitats tend to contain lineages dating back to warm and dry epochs. Identifying lineages from sets of random time intervals rather than from a set of geological epochs significantly reduced relationships with the environment. Main conclusions Within a region, habitat types differ significantly in the evolutionary heritage they contain from different geological epochs, and these differences are controlled by the environment.

‘High‐co‐occurrence genera’: weak but consistent relationships with global richness, niche partitioning, hybridization and decline - Andreas Prinzing; Leslie W. Powrie; Stephan M. Hennekens; Igor V. Bartish; Wim A. Ozinga (Global Ecology and Biogeography, 2016)
Aim Many biologists explain the global richness of lineages and local co‐occurrence of lineage members by distinct processes: speciation/extinction versus ecological interactions. Moreover, allopatric distribution, rarity and local competition limit local co‐occurrence of species even within species‐rich lineages. However, whether and why the global richness of lineages relates to local co‐occurrence of lineage members has not been tested. We study angiosperms, and hypothesize that in globally species‐rich genera species frequently encounter congeners locally, reflecting (1) random sampling of species pools into local communities and (2) processes of global species production and local survival such as hybridization, niche filling and a reduced risk of extinction. Location N etherlands, S outh A frica, world‐wide. Methods Analysing more than 350,000 plots we quantify per species the observed number of co‐occurring congeners as well as the null expectation based on random sampling from species pools. From the literature we quantify the global species richness of genera, and abiotic niche positions and breadths, hybrid status and regional species declines. Results In some genera species frequently encounter congeners locally, while in others congeners are rarely encountered. This is independent of the total number of species encountered, and is consistent between the N etherlands and S outh A frica. ‘High‐co‐occurrence genera’ are particularly species rich across the globe, consistently so in most families and even after controlling for niche positions, age and regional richness of genera. Species in high‐co‐occurrence genera tend to occupy niches that are large and close to congeners’ niches. These species are more often hybrids and rarely decline. Relationships explain little variance ( Main conclusions Local co‐occurrence and global species richness are largely independent, but not entirely so, reflecting random sampling of pools into communities, niche partitioning, hybridization and the reduced risk of regional extinction in high‐co‐occurrence genera. Increased extinction risk in low‐co‐occurrence genera implies a proportionately high loss of lineages and their evolutionary heritage from local communities.

Explaining the disjunct distributions of austral plants: the roles of Antarctic and direct dispersal routes - Richard C. Winkworth; Françoise Hennion; Andreas Prinzing; Steven J. Wagstaff (Journal of Biogeography, 2015)
Aim Dispersal explains the disjunct distributions of many austral plant lineages. However, the role of Antarctica is largely uncertain and the routes of dispersal have remained speculative. Based on niche conservatism we can make predictions about the timing of disjunction establishment, as well as the availability of direct transoceanic, Antarctic stepping‐stone, and out‐of‐Antarctica dispersal routes over time. We evaluate these predictions using molecular divergence time estimates for the establishment of disjunct distributions across multiple plant lineages. Location Southern Hemisphere. Methods We estimated the timing of disjunction establishment and determined habitat affinities for 72 austral plant groups. We used Wilcoxon rank sum tests to compare the timing of disjunction establishment between cold and temperate climate lineages for the full data set, as well as within several subsets. We compared our results with those from a literature survey. Results As niche conservatism predicts, the timing of disjunction establishment in cold and temperate climate austral lineages is consistent with the availability of the corresponding habitats over time. Our results also suggest that disjunction establishment has involved a combination of Antarctic and direct dispersal routes. For cold climate lineages, both out‐of‐Antarctica and direct dispersal routes are required to explain the observed estimates, while stepping stone routes cannot be ruled out. It appears that for these lineages the importance of the three dispersal routes differs with environmental, geographical and temporal context. Main conclusions Both direct and Antarctic dispersal routes are necessary to explain the establishment of contemporary austral distributions. Evidence that some taxa were, until recently, restricted to Antarctica changes how we view the evolutionary histories of austral floras and the lineages they contain. Moreover, that we detect differences in the importance of alternative dispersal routes suggests that long‐distance plant dispersal processes can be explicitly incorporated into models of climate change response.

Insect herbivores should follow plants escaping their relatives - Benjamin Yguel; Richard Ian Bailey; Claire Villemant; Amaury Brault; Hervé Jactel; Andreas Prinzing (Oecologia, 2014)

Species living in harsh environments have low clade rank and are localized on former Laurasian continents: a case study of Willemia (Collembola) - Andreas Prinzing; Cyrille A. D'Haese; Sandrine Pavoine; Jean‐François Ponge (Journal of Biogeography, 2014)
Aim Certain species have few living relatives (i.e. they occupy low clade ranks) and hence they possess high conservation value and scientific interest as unique representatives of ancient lineages. However, we do not know whether particular environments favour the maintenance of low clade ranks or whether the distribution of environments across the globe affects the global distribution of clade ranks and, hence, evolutionary uniqueness. In this study, we tested whether and how harsh environments decrease the clade ranks of the species that inhabit them. Location Global. Methods We described the phylogeny of the collembolan genus Willemia by a parsimonious method based on 52 morphological characters and estimated the species' use of harsh environments (polar, high mountain, desert, polluted, waterlogged, saline and acidic) from 248 publications. Results We found that the use of different types of harsh environments is maintained among close relatives and has similar phylogenetic signals (except for the use of salinity). The use of harsh environments might therefore affect the diversification of lineages. Correcting for the phylogenetic non‐independence of species, we found that species using harsh environments have comparatively low clade ranks. We also found that species using harsh environments occur almost exclusively on former Laurasian continents and that, as a statistical consequence, Laurasian species tend to have lower clade ranks. Main conclusions We suggest that harsh environments maintain low‐clade‐rank species by decreasing, simultaneoulsy or successively, extinction and speciation, which may eventually explain the major variation in clade rank across the globe.

Endemic species have highly integrated phenotypes, environmental distributions and phenotype–environment relationships - Marie Hermant; Andreas Prinzing; Philippe Vernon; Peter Convey; Françoise Hennion (Journal of Biogeography, 2013)
Aim Why are some species geographically restricted? Ecological explanations suggest that endemic species may have restricted distributions because limited phenotypic variability results in narrow niches. However, studying variability of traits independently may not fully explain the interactions within and between complex phenotypes and environments. Here, we hypothesize that endemic species are restricted to a narrow range of habitats due to strong phenotypic integration (i.e. strong correlations among traits), strong environmental integration (i.e. strong correlations among the environments occupied) and strong correlations among trait–environment combinations. Location The Kerguelen Islands, sub‐Antarctic. Methods We measured flowering phenology, multiple morphological characters, and species distribution along three abiotic environmental gradients (elevation, soil moisture and soil salinity) in 14 plant species whose distributions range from strictly endemic to cosmopolitan. Results We found that for individual species, trait means and variances were independent of endemism, but that endemics occupied higher and less variable microhabitats. However, phenotypic integration, environmental integration along the three gradients, and the strength of trait–environment correlations all increased with the level of species endemism. Main conclusions Higher levels of integration within and between phenotypes and environments are associated with more restricted geographical ranges in the species studied. In endemic species phenotypic integration may explain range contraction during the taxon cycle and reduce the ability to adapt to novel microhabitats formed as a result of environmental change.

Specialists leave fewer descendants within a region than generalists - Wim A. Ozinga; Audrey Colles; Igor V. Bartish; Françoise Hennion; Stephan M. Hennekens; Sandrine Pavoine; Peter Poschlod; Marie Hermant; Joop H. J. Schaminée; Andreas Prinzing (Global Ecology and Biogeography, 2013)
Aim Current conservation biology suggests that across ecological time‐scales specialist species existing in the recent past have left on average fewer descendant populations today than generalist species. Conversely, the speciation literature suggests that on an evolutionary time‐scale specialists leave as many or more descendant lineages as generalists, i.e. they have high rates of global diversification. This begs the question: which of these two processes has more influence on the regional scale, i.e. do specialists leave more or fewer descendants than generalists within a region? Location The flora of the N etherlands. Methods We quantified niche volume of 707 plant species from coexistence data and ecological indicator values and used sister taxon comparisons to compare specialist and generalist sister taxa for the relative numbers of descendants across three temporal scales: ecological, microevolutionary and macroevolutionary. Results We show, first, that specialist species are more likely to be currently declining, i.e. to leave only few descendant populations. Second, specialists are less likely to be currently diversifying into intra‐specific taxa. Finally, most specialist clades left fewer descendant species within a region than their generalist sister clades. These results were consistent across sublineages, unbiased by geographic sampling of lineages and environments, and held after accounting for species life histories. Differences between specialist and generalist sister clades increased with clade age, suggesting that they reflect differences in rates at which specialists left descendants (rather than differences in ecological limits to the numbers of specialists and generalists). Main conclusions Specialists left only few descendants within a region (i.e. the N etherlands), both at ecological, microevolutionary and macroevolutionary scales. While specialists may leave numerous evolutionary descendants at a global scale, these might be absent from most regions. Humans, by threatening specialist species, may hence further accelerate biotic homogenization with descendants of generalist lineages proliferating within regions while specialist lineages disappear.

Species pools along contemporary environmental gradients represent different levels of diversification - Igor V. Bartish; Stephan Hennekens; Ahmed Aidoud; Françoise Hennion; Andreas Prinzing (Journal of Biogeography, 2010)
Aim Within a region, different habitat types are characterized by different species and some habitat types have higher species diversities than others. Different habitat types are also characterized by different phylogenetic clades. However, it is not known whether – within a given region – some habitat types have species pools that are more phylogenetically diversified than others. We investigated whether species pools in contemporary habitat types represent different levels of diversification of angiosperms and, if so, whether these differences correlate with particular environmental factors. We tested these relationships in a region of recent geological origin possessing a comparatively young flora, and compared the result with standard analyses of species diversity. Location The Netherlands. Methods We studied angiosperms across the full range of habitat types present in the Netherlands. We characterized levels of diversification represented in species pools within each of these habitat types with respect to (1) taxonomic diversification, i.e. the rate of increase of richness across taxonomic ranks (relative to a null expectation for a given species richness), and (2) cladogenic diversification, i.e. the average cladogenic distance of species from the root of a phylogenetic tree of the species pool within a given region. Results Species pools of different habitat types represented different levels of taxonomic and cladogenic diversification. These differences were strongly correlated with the environmental characteristics of the habitat type. Greater levels of taxonomic diversification were represented in the species pools of relatively dry and open habitat types. Greater levels of cladogenic diversification were represented in habitats with both dry and weakly acidic soils. The relationship between environmental factors and taxonomic and cladogenic diversification ( r 2 = 0.88 and 0.76, respectively) was stronger than that between environmental factors and species richness ( r 2 = 0.34). Main conclusions Within a region, species resulting from particularly high rates of diversification accumulated in particular habitat types. These habitat types represent specific contemporary abiotic environments and have a tighter relationship with levels of diversification than with species richness.

Are specialists at risk under environmental change? Neoecological, paleoecological and phylogenetic approaches - Audrey Colles; Lee Hsiang Liow; Andreas Prinzing (Ecology Letters, 2009)
The question ‘what renders a species extinction prone’ is crucial to biologists. Ecological specialization has been suggested as a major constraint impeding the response of species to environmental changes. Most neoecological studies indicate that specialists suffer declines under recent environmental changes. This was confirmed by many paleoecological studies investigating longer‐term survival. However, phylogeneticists, studying the entire histories of lineages, showed that specialists are not trapped in evolutionary dead ends and could even give rise to generalists. Conclusions from these approaches diverge possibly because (i) of approach‐specific biases, such as lack of standardization for sampling efforts (neoecology), lack of direct observations of specialization (paleoecology), or binary coding and prevalence of specialists (phylogenetics); (ii) neoecologists focus on habitat specialization; (iii) neoecologists focus on extinction of populations, phylogeneticists on persistence of entire clades through periods of varying extinction and speciation rates; (iv) many phylogeneticists study species in which specialization may result from a lack of constraints. We recommend integrating the three approaches by studying common datasets, and accounting for range‐size variation among species, and we suggest novel hypotheses on why certain specialists may not be particularly at risk and consequently why certain generalists deserve no less attention from conservationists than specialists.

Dispersal failure contributes to plant losses in NW Europe - Wim A. Ozinga; Christine Römermann; Renée M. Bekker; Andreas Prinzing; Wil L. M. Tamis; Joop H. J. Schaminée; Stephan M. Hennekens; Ken Thompson; Peter Poschlod; Michael Kleyer; Jan P. Bakker; Jan M. Van Groenendael (Ecology Letters, 2009)
The ongoing decline of many plant species in Northwest Europe indicates that traditional conservation measures to improve the habitat quality, although useful, are not enough to halt diversity losses. Using recent databases, we show for the first time that differences between species in adaptations to various dispersal vectors, in combination with changes in the availability of these vectors, contribute significantly to explaining losses in plant diversity in Northwest Europe in the 20th century. Species with water‐ or fur‐assisted dispersal are over‐represented among declining species, while others (wind‐ or bird‐assisted dispersal) are under‐represented. Our analysis indicates that the ‘colonization deficit’ due to a degraded dispersal infrastructure is no less important in explaining plant diversity losses than the more commonly accepted effect of eutrophication and associated niche‐based processes. Our findings call for measures that aim to restore the dispersal infrastructure across entire regions and that go beyond current conservation practices.

Less lineages – more trait variation: phylogenetically clustered plant communities are functionally more diverse - Andreas Prinzing; Reineke Reiffers; Wim G. Braakhekke; Stephan M. Hennekens; Oliver Tackenberg; Wim A. Ozinga; Joop H. J. Schaminée; Jan M. Van Groenendael (Ecology Letters, 2008)
Functional diversity within communities may influence ecosystem functioning, but which factors drive functional diversity? We hypothesize that communities assembled from many phylogenetic lineages show large functional diversity if assembly is random, but low functional diversity if assembly is controlled by interactions between species within lineages. We combined > 9000 descriptions of Dutch plant communities, a species‐level phylogeny, and information on 16 functional traits (including eight dispersal traits). We found that all traits were conserved within lineages, but nevertheless communities assembled from many lineages showed a smaller variation in trait‐states of most traits (including dispersal traits) than communities assembled from few lineages. Hence, within lineages, species are not randomly assembled into communities, contradicting Neutral Theory. In fact, we find evidence for evolutionary divergence in trait‐states as well as present‐day mutual exclusion among related, similar species, suggesting that functional diversity of communities increased due to past and present interactions between species within lineages.

The trade‐off between vegetative and generative reproduction among angiosperms influences regional hydrochorous propagule pressure - Ger Boedeltje; Wim A. Ozinga; Andreas Prinzing (Global Ecology and Biogeography, 2008)
Aim Local communities are subject to spatiotemporal contingencies of landscape processes; community assembly is thus often considered to be unpredictable and idiosyncratic. However, evolved trade‐offs of species’ life histories may set distinct constraints on the assembly of species communities. In plants, the recruitment and invasion success of species into communities depend primarily on the number of propagules available and on their generative or vegetative character. Life‐history trade‐offs prevent individual plants from producing large numbers of both generative and vegetative propagules, but it is not clear whether this constrains their availability at the landscape scale. We thus tested whether: (1) the observed relationship between generative and vegetative propagules deviates from the null expectation stating that species contributing the bulk of generative propagules to the propagule rain should also contribute the bulk of vegetative propagules; and (2) whether vegetative and generative propagule pressures are negatively correlated once species abundance in the regional pool is accounted for. Location A large riparian landscape in the Netherlands. Methods Analyses were based on an extensive trapping of floating propagules (214,049 propagules of 47 species), and a rough proxy of species abundance across the entire pool. We used both species and phylogenetically independent contrasts as data points, and accounted for variation in size of generative propagules. Results Both hypotheses were confirmed. Numbers of generative and vegetative propagules trapped per species were significantly negatively correlated ( r = −0.33; t 45 = −2.61, P = 0.006) and thus strongly deviated from the null expectation. This was confirmed by analyses accounting for variation in species abundance across the species pool, and in the size of generative propagules. Main conclusions The results indicate that plant recruitment and community assembly across streams may be influenced by the way individual plants allocate their resources between competing life‐history functions. Life‐history evolution across angiosperms might thus have constrained the present‐day assembly of local communities.